Phenomenology Of Delirium: A Cross-Sectional Study Among Referred Cases Of Delirium - Verma, S K; Pandey, A K; Adhikari, B R; Mallick, L (Journal of Psychiatrists’ Association of Nepal, 2015)
Introduction: Studies from developing countries are few, on phenomenology of Delirium, even though it is a common diagnosis among psychiatric referrals. We studied the phenomenology of delirium in a teaching hospital in western region of Nepal by using standard assessment methods. Aim: The aim of the study was to assess the phenomenological characteristics of delirium based on Delirium Rating Scale-Revised-98 (DRS–R98). Methods: All consecutive patients of delirium who were referred to department of psychiatry for assessment were enrolled over a period of 12 months. Socio-demographic variables and other medical information were collected by using standardized data-collection forms developed by the department of Psychiatry. Assessments were based on all available information obtained from the patients, caregivers, medical staff, and medical records. Results and conclusions: A total of 62 cases were studied out of which 83.9% were male. Mean age of the subjects was 47 years. Mean delirium severity was 21.35 (SD=3.54). Orientation, attention and short term memory was impaired in all of the cases. Long term memory impairment was noted in 98.4% of cases. Sleep wake cycle disturbance was present in 60 (96.8%) cases, perceptual abnormalities in 49 (79%) cases, some form of delusion was present in 19 (30.6%), lability of affect could be appreciated in 27(43.5%). Language, thought process abnormalities and impaired visuo-spatial ability was present in 19 (30.6%), 3 (4.8%) and 13 (21%) cases respectively. J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 43-47 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12394